What is distinctive about New Zealand's Employment Relations Act 2000?. (2nd January 2019) - Rasmussen, Erling; Bray, Mark; Stewart, Andrew
ABSTRACT: This article aims to analyse New Zealand's Employment Relations Act 2000 (ERA) in a historical perspective and identify its distinctive features compared to three previous labour law regimes: the last phases of the conciliation and arbitration system (1973–1984 and 1984–1991) and the Employment Contracts Act (1991–2000). The article draws on an analytical approach first applied to analyse the historical position of the Fair Work Act in Australia. This approach identifies the significance and level of priority accorded to different processes of rule-making under each of the regimes. It shows that since 1973 there has been considerable change in New Zealand labour law. The most conspicuous is the decline of delegated regulation as industrial tribunals and their awards have lost their previously central role. Collective agreement-making has fared only marginally better. The 'long shadow' of the Employment Contracts Act can still be detected in the minimal role of delegated regulation and the much reduced role of collective agreement-making. It is, therefore, the very dynamic and unresolved contest between, on the one hand, individual contracting and, on the other hand, more comprehensive and detailed statutory regulation, that makes the ERA distinctive compared to previous frameworks.